The sustainability of public debt - Merza, Ebrahim; & Alaaeddin Al-Tarawneh, Eman Maghareez, Mohammad Alawin (Opción, 2019)
The primary objective of this study to examine the sustainability of public finance and debt in Jordan. This paper will use the method of Fully Modified Least Squares (FMOLS). The results show that public finance is unable to stabilize the ratio of public debt to GDP at the target. However, for some measures, there was the sustainability of public debt, but it was weak. In conclusion, it is necessary to comprehensively review all items of the public expenditure, prevent unnecessary spending, and direct spending towards productive projects